SH2-containing PTPs (Shps) in RTK signaling and disease - Neel, Benjamin G. (Henry Stewart Talks, 2007)
Introduction to the PTP superfamily, Shps, history and overview, Shp stucture: role of SH2 domains, PTP domains, C-tail, catalytic mechanism, Regulation by phosphotyrosyl peptides, phosphorylation, reactive oxygen species, Overview of physiological functions, Role in RTK signaling: regulation of Ras/Erk pathway; roles in other downstream cascades, Shps in disease, Key questions and challenges for the future
Archived at 2018/05/31